A EXTENSÃO DA RESPONSABILIDADE DOS SÓCIOS DE SOCIEDADE LIMITADA NO CÓDIGO CIVIL - Campos, Aline França (Revista da AJURIS - Qualis A2, 2012)
THE EXTENT OF LIMITED LIABILITY PARTNERSHIP IN THE (BRAZILIAN) CIVIL CODE RESUMO: O próprio Código Civil, que estabelece expressamente a limitação de responsabilidade dos sócios de sociedades limitada ao valor de suas quotas, prevê ainda hipóteses de responsabilização pessoal dos mesmos por obrigações contraídas pela sociedade. Prevê a responsabilidade pessoal e solidária de todos os sócios pela completa integralização do capital social subscrito. Na mesma esteira, estabelece também responsabilidade solidária entre todos os sócios pela exata estimação do valor dos bens conferidos ao capital social. Por fim, prevê a responsabilidade daqueles sócios que contribuírem com seus votos para aprovação, em assembleia geral ou reunião, de deliberação infringente da lei ou do contrato social. PALAVRAS-CHAVE: Sociedade limitada; responsabilidade dos sócios; exceções à limitação de responsabilidade. ABSTRACT: The partners, as established in the article 1.052 of the Civil Code of 2002, have liability restricted to the value of their shares. Despite such limitation be essential for setting the institute of limited liability companies, the Civil Code itself provides several hypotheses of personal liability of the partners. Provides personal responsibility and solidarity of all members for the full payment of the subscribed capital. In the same vein, also establishes joint responsibility among all partners by accurately estimating the value of property vested in the capital. Finally, it provides for the responsibility of those members who contribute with their votes for approval in general meeting or meeting of deliberation infringing the law or the social contract. KEYWORDS: Limited liability company; liability of partners and administrators; exceptions to the limitations of liability. SUMÁRIO: Introdução; 1 Garantia de integralização de todo capital social (artigo 1.052 do CC/2002); 2 Responsabilidade pela exata estimação do valor dos bens conferidos ao capital social (artigo 1.055, § 1º, do CC/2002); 3 Responsabilidade do sócio que contribuir, com seu voto, para uma deliberação infringente da lei ou do contrato social (artigo 1.080 do CC/2002); 4 Cessão e trespasse; Conclusão: a desconfiguração do instituto das sociedades limitadas; Referências. SUMMARY: Introduction; 1 Guarantee payment of the entire share capital; 2 Responsibility for accurate estimation of the value of the property vested in the capital; 3 Accountability partner who contribute, through their vote, a resolution for infringing the law or the social contract; 4 Assignment and leasehold; Conclusion: the mangling of the Institute of limited partnerships; References.